Widespread positive selection in the photosynthetic Rubisco enzyme - Kapralov, M; Filatov, D (BioMed Central, 2007)
Background: Rubisco enzyme catalyzes the first step in net photosynthetic CO2 assimilation and photorespiratory carbon oxidation and is responsible for almost all carbon fixation on Earth. The large subunit of Rubisco is encoded by the chloroplast rbcL gene, which is widely used for reconstruction of plant phylogenies due to its conservative nature. Plant systematicists have mainly used rbcL paying little attention to its function, and the question whether it evolves under Darwinian selection has received little attention. The purpose of our study was to evaluate how common is positive selection in Rubisco among the phototrophs and where in the Rubisco structure does positive selection occur. Results: We searched for positive selection in rbcL sequences from over 3000 species representing all lineages of green plants and some lineages of other phototrophs, such as brown and red algae, diatoms, euglenids and cyanobacteria. Our molecular phylogenetic analysis found the presence of positive selection in rbcL of most analyzed land plants, but not in algae and cyanobacteria. The mapping of the positively selected residues on the Rubisco tertiary structure revealed that they are located in regions important for dimer-dimer, intradimer, large subunit-small subunit and Rubisco-Rubisco activase interactions, and that some of the positively selected residues are close to the active site. Conclusion: Our results demonstrate that despite its conservative nature, Rubisco evolves under positive selection in most lineages of land plants, and after billions of years of evolution Darwinian selection still fine-tunes its performance. Widespread positive selection in rbcL has to be taken into account when this gene is used for phylogenetic reconstructions.